The effect of pineapple peel and chicken bone flours on the physicochemical properties and sensory acceptability of noodles - Agustin, Nur; Mahmudah, Nur Aini; Purnomo, Panji (Universitas Slamet Riyadi Surakarta, 2026)
Wheat has limited nutritional content, therefore fortification with other ingredients is required to complement these nutrients, one of which is fortification with pineapple peel flour and chicken bones in noodle products. Thus, this study was conducted to investigate the impact of adding chicken bone and pineapple peel flours on the characteristics of wheat flour noodles, with the goal of developing a product enriched in fiber and minerals, and exhibiting acceptable sensory qualities. The research design used a completely randomized design (CRD) with 2 experimental factors, namely pineapple peel flour concentration (0%,3%,5%) and chicken bone flour concentration (0%,5%,10%) with triplicate replication. Based on the optimal treatment by Zeleny method, sample N1T3 emerged as the most favorable formulation. This sample exhibited the following chemical profile: a moisture content of 8.77%, an ash content of 4.52%, a protein content of 14.45%, a fat content of 1.52%, and a fiber content of 0.4%. Furthermore, sensory evaluation of Sample C yielded scores of 3.11 for color, 3.11 for aroma, 3.00 for taste, 2.89 for texture, and 2.89 for overall acceptance.